Chemical properties and decay resistance of eucalyptus grandis wood from steamed logs - Rocha, Cinthia Dias [UNESP]; Severo, Elias Taylor Durgante [UNESP]; Calonego, Fred W'illians [UNESP]; Sansígolo, Cláudio Angeli [UNESP] (My University, 2012)
The objective of this study was evaluate the effect of the log steaming on the chemical properties and decay resistance of Eucalyptus grandis wood. Logs with diameter between 20 and 22 cm were studied. Half of logs were kept in its on original condition, and the other half was steamed at 90°C for 13 hours. The holocellulosc, Klason lignin, total extractives content and the weight loss caused by the decay fungus Pycnoporus sanguineous were characterized. The results showed that the log steaming of E. grandis wood cause: (l)a significantly decreased in holocellulose content; (2) an increase of 4.8% and 4.4% in total extractives and lignin content, respectively; and (3) a decrease in its durability against the decay fungus P. sanguineus in order of 13.03%. Copyright © (2012) by WCTE 2012 Committee.
Keywords: Chemical properties; Eucalyptus grandis; Log steaming; Pycnoporus sanguineous; Decay fungi; Decay resistance; Extractives content; Holocellulose; Klason lignin; Lignin contents; Weight loss; Decay (organic); Lignin; Timber